Revisión especial a las cuentas de ingresos y egresos y su incidencia en el resultado económico de la cooperativa de taxi San Jacinto, cantón Buena Fe, año 2013 - Rodríguez Zamora, Cristhian Ricardo (2015)
The Special Review is the run on the Cooperative Taxi San Jacinto Canton Good Faith, the Income and Expenditure, 2013, as General Purpose was raised Run a Special to the Accounts Income and Expenditure Review and its impact on economic results Taxi Cooperative to San Jacinto, Canton Good Faith, 2013; The specific objectives Establish the level of compliance with the Law on Popular and Solidarity Economy, based on the correct institutional performance; Evaluate internal control processes for measuring accrued income and expenses; Examine the accounting process of the Cooperative to determine the reliability and fairness of income and expenses and issue a Special Review Report as perspective to improve the consistency of Revenues and Expenditures. We begin with the preliminary information Taxi Cooperative San Jacinto to be examined by studying the company in its different stages from its inception. Besides the theoretical conceptualization which gives greater importance to the Special Review it is implemented, supporting based on the techniques and procedures that an auditor must employ. Finally, the Final Report of Special Review showing comments, conclusions and recommendations is provided, which enable the highest authority of the cooperative take the corrective measures that it deems appropriate.